(untitled) (Romano-arabica, 2025)
Arabic is recognized as one of the most prominent and widely spoken languages globally (Amara, 2024: 69), attracting numerous learners due to its historical and cultural significance. It is acknowledged as the mother tongue and national language of Arab Palestinians, a language of the Middle East, closely related to Hebrew, and a language of cultural heritage for nearly half of the Jewish population in Israel (Graysi, 2018). In Hebrew academia, Arabic has been continuously taught from 1948 to the present day. Despite the presence of universities and colleges specializing in Arabic instruction, educational practices reveal significant disparities in objectives and curricula across different institutions. This variability poses substantial challenges to the development and enhancement of Arabic education and its academic standing. Providing a sociolinguistic study of the status of Arabic in Hebrew academia, this article aims to decode the challenges and explore the perspectives of teaching Arabic. It will identify the conditions and context of teaching Arabic as a second language. By examining sociolinguistic theory and referencing precise examples and sources, we seek to provide a comprehensive overview and in-depth analysis, to evaluate the current academic reality of Arabic language teaching in Hebrew universities, and to describe the main obstacles to creating an academic environment that effectively encourages balanced and active language learning.